Segregation- and association based mapping of loci influencing osmotic tolerance in barley - Bálint, András Ferenc (Acta Biologica Szegediensis, 2008)
Identifying quantitative trait loci (QTLs) influencing abiotic stress tolerance could speed up the breeding process via marker assisted selection (MAS), however the accuracy of QTL analysis is a limiting factor to use successfully the identified marker alleles. We used a new approach to map more accurately the loci affecting osmotic tolerance in barley, which permit the introduction of MAS in the breeding process of new and more tolerant varieties against abiotic stresses.